2013
DOI: 10.1086/667691
|View full text |Cite
|
Sign up to set email alerts
|

Money and Thinking: Reminders of Money Trigger Abstract Construal and Shape Consumer Judgments

Abstract: The idea of money reminds consumers of personal strength and resources. Such cues have been found to increase the level of mental construal. Consequently, it was hypothesized and found in five experiments that reminders of money trigger abstract (vs. concrete) mental construals. Participants were primed with money or money-unrelated concepts. Money primes caused a preference for abstract over concrete action identifications (experiment 1), instigated the formation of broader categories (experiment 2), and faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 51 publications
4
68
0
1
Order By: Relevance
“…That is, the larger an amount of money is, the more abstractly it is construed (MacDonnell and White 2015; see also Hansen, Kutzner, and Wänke 2013). Because construal level is a "common currency" that allows one dimension of psychological distance to subadditively affect a separate dimension of psychological distance (Bar Anan et al 2007;Fiedler et al 2012), it stands to reason that cross-dimensional subadditivity might extend to any two dimensions that share a similar effect on construal.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the larger an amount of money is, the more abstractly it is construed (MacDonnell and White 2015; see also Hansen, Kutzner, and Wänke 2013). Because construal level is a "common currency" that allows one dimension of psychological distance to subadditively affect a separate dimension of psychological distance (Bar Anan et al 2007;Fiedler et al 2012), it stands to reason that cross-dimensional subadditivity might extend to any two dimensions that share a similar effect on construal.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous work shows that reminders of money can change behavior (Hansen, Kutzner, and Wänke 2013;Kouchaki et al 2013;Piff 2013;Tong, Zheng, and Zhao 2013;Goode 2006, 2008) -for example, by heightening feelings of independence and selfsufficiency, reducing willingness to help, and diminishing how much people care about social exclusion (Vohs et al 2006;Zhou, Vohs, and Baumeister 2009). It could be interesting to test whether these effects depend on whether the money belongs to the self versus others.…”
Section: Practical Implications and Future Directionsmentioning
confidence: 99%
“…Since the descrambling task has been used in previous research to successfully induce money priming (e.g. Hansen et al, 2013) we do not think that this necessarily weakens our results. Still, this point is worth mentioning as a direction for future research.…”
Section: Discussionmentioning
confidence: 68%
“…All studies had in common that participants worked on two ostensibly unrelated experiments. Across all studies the first experiment was a money priming manipulation that was framed as a task on playful language learning methods and comprised a descrambling sentence task (see Hansen, Kutzner, & Wänke, 2013). The second experiment was framed as a study on decision-making and contained one of the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that such 'money priming' affects cognitions, emotions, and behavior. It has been shown, for instance, that priming with the idea of money changes cognitive processes (Hansen et al, 2013); mere reminders of money, such as pictures of money or thinking about the concept of money, trigger abstract (versus concrete) mental representations and an abstract style of thinking. For instance, participants who are primed with money represent actions more in terms of their abstract goals instead of their concrete means, they perceive the world in fewer and broader (instead of more and narrower) categories, and they are relatively quicker in identifying global pictures ('the forest') and relatively slower in identifying local details ('the trees').…”
Section: Thinking About Moneymentioning
confidence: 99%